2010
DOI: 10.1186/1747-597x-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Potentially harmful advantage to athletes: a putative connection between UGT2B17 gene deletion polymorphism and renal disorders with prolonged use of anabolic androgenic steroids

Abstract: Background and objectiveWith prolonged use of anabolic androgenic steroids (AAS), occasional incidents of renal disorders have been observed. Independently, it has also been established that there are considerable inter-individual and inter-ethnic differences, in particular with reference to the uridine diphosphate-glucuronosyltransferase 2B17 (UGT2B17) gene, in metabolising these compounds. This report postulates the association of deletion polymorphism in the UGT2B17 gene with the occurrence of renal disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
0
22
0
3
Order By: Relevance
“…Similarly, in another study carried out by Shen et al stanozolol was detectable in guinea pig hair after administering stanozolol at a single high dose of 60 mg/kg, whereas, 3'-hydroxystanozolol was not detectable [20]. However, the method developed for the current study is capable of detecting stanozolol and 3'-hydroxystanozolol in rat hair after administering stanozolol for 6 days at a dose of 5.0 mg/kg/day that is considered equivalent to those levels abused by athletes [6].…”
Section: Implications Of Results and Future Perspectivesmentioning
confidence: 57%
“…Similarly, in another study carried out by Shen et al stanozolol was detectable in guinea pig hair after administering stanozolol at a single high dose of 60 mg/kg, whereas, 3'-hydroxystanozolol was not detectable [20]. However, the method developed for the current study is capable of detecting stanozolol and 3'-hydroxystanozolol in rat hair after administering stanozolol for 6 days at a dose of 5.0 mg/kg/day that is considered equivalent to those levels abused by athletes [6].…”
Section: Implications Of Results and Future Perspectivesmentioning
confidence: 57%
“…Additional consistent report has represented that in chromosome 2 PPM1B gene, which is recognized as one of the genes with high frequency in the homozygous deletion of 179 kb, leading to 2p21 deletion syndrome 15 . Also, on chromosome 4 the homozygous loss and loss at identified region of UGT2B17 (uridine diphosphate-glucuronosyltransferase 2B17) gene encoding an enzyme participating in steroid hormones catabolism 16 . A potential link between deletion polymorphism in UGT2B17 gene and renal disorders has been observed in athletes with prolonged use of anabolic androgenic steroids 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, on chromosome 4 the homozygous loss and loss at identified region of UGT2B17 (uridine diphosphate-glucuronosyltransferase 2B17) gene encoding an enzyme participating in steroid hormones catabolism 16 . A potential link between deletion polymorphism in UGT2B17 gene and renal disorders has been observed in athletes with prolonged use of anabolic androgenic steroids 16 . Other study has revealed involvement of deletion variant UGT2B17 in CNV 4q13.2 for osteoporotic pathogenesis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This report of a straightforward novel method of rapid analyses of testosterone and epitestosterone in both rat urine and sera benefits from a new rapid liquid-liquid extraction procedure, suitable for both biofluids. Unlike the predecessors, the proposed method streamlines experimental in vivo designs where simultaneous monitoring of testosterone and epitestosterone in both urine and blood is required, such as investigating the effect and consequences of altered metabolic function in testosterone and epitestosterone glucuronidation [7][8][9][10]. The new method also eliminates potential confounding effects from applying multiple methods to cater for multiple sample matrices.…”
Section: Application Of Methods For Determination Of Testosterone and mentioning
confidence: 98%
“…Variations in enzyme preference are observed with UGT 2B17 predominating for testosterone glucuronidation, whilst UGT2B7 is the most active UGT for epitestosterone glucuronidation [5]. A variety of effectors of steroid UGT glucuronidation have been identified, including pharmacogenetic variations resulting in different UGT2B17 expression which affects the urinary T/E ratios [6][7][8]. A number of in vitro studies have identified small molecule inhibitors of UGT2B17 and other UGTs toward testosterone metabolism.…”
Section: Introductionmentioning
confidence: 99%